Natural Automatic Musical Note Player using Time-Frequency Analysis on Human Play - Khafiizh Hastuti; Arry Maulana Syarif; Ahmad Zainul Fanani; Aton Rustandi Mulyana (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
This research aims to develop an automatic gamelan musical note player that can naturally play musical note as human does. A musician estimates time to hit an instrument button in an approximate time which is as close as to the target time. The tolerated time to play a note was identified based on the human play. A gamelan musician was selected to play five note sequences of songs, and the play was recorded to be analyzed. Execution time in hitting instrument buttons in human play was identified using time-frequency analysis and peak detection to define time range which can be tolerated as time value that not too fast or not too late in hitting buttons, and then the result of the analysis was used as parameters to randomize approximate time to play a note. The evaluation shows that the program played all note sequences in the approximate time as human does and the program played more natural and better than another program which played a note as exact as its time target.